Pembuatan Pedoman Proses Rekruitmen dan Seleksi Berbasis Digital Booklet pada PT Ebiz Prima Nusa - Putri Kumara Dennis; Sri Surjani Tjahjawati (Applied Business and Administration Journal, 2023)
Recruitment and selection processes Project planning and smart hiring are two things needed to obtain quality employees, namely employees who are smart, skilled, have competence, can work, are creative, and have high morality. However, in its implementation, the recruitment and selection process at PT Ebiz Prima Nusa has not been carried out effectively. Such as the absence of references, guidelines, or standardization when recruitment and selection are carried out. Based on this phenomenon, a project was developed to create media that can provide complete information in the form of a digital booklet regarding the recruitment and selection process at PT Ebiz Prima Nusa. The digital booklet created aims to serve as a guideline, direction, and reference for recruitment and selection activities. This project was made with qualitative methods for collecting data and processed with the interactive model method. The project design was carried out with the help of the Canva and Anyflip platforms so that the digital booklet could be created. The design stage is divided into three stages: pre-project implementation, project implementation, and post-project implementation. In the pre-project implementation stage, problem identification, a literature review, and needs interviews were conducted. Furthermore, the project implementation stage is also carried out in stages, starting with planning, information processing, searching for a digital booklet platform, design, development, testing, revision conducted by interviews with experts or lecturers, Forum Group Discussions (FGD) with employees who have been accepted at the testing stage, and interviews with HR, then ending with the publication stage. The last stage is post-implementation, which involves reviewing the impact of the project through a final interview. The final result of this project is a digital booklet that will be used as a guideline, direction, and reference for recruitment and selection activities at PT Ebiz Prima Nusa.